High-risk children and social isolation: the importance of family functioning - Maria Fernanda Vieira; Maria Dalva Barbosa Baker Méio; Maria Dalva Barbosa Baker Méio; Ana Beatriz Rodrigues Reis; Letícia Duarte Villela; Maura Calixto Cecherelli de Rodrigues; Fátima Cristiane Pinho de Almeida Di Maio Ferreira; Letícia Baptista de Paula Barros; Roozeméria Pereira Costa; Elaine Rego Menezes; Camila Oliveira Campos; Maria Elisabeth Lopes Moreira; et al. (Frontiers in Psychology, 2023)
High-risk newborns are exposed to neonatal conditions such as prematurity, very low birth weight, and congenital malformations that can affect development and behavior. Coronavirus disease 2019 (COVID-19) restraint and control measures have been identified as important stressor events and cumulative risk factors for behavioral changes in these children. This study examined social isolation-related factors that contribute to internalizing and externalizing behavior problems in children already at risk for neurodevelopmental disorders. This cross-sectional, multicenter study included 113 children (18 months to 9 years) who were followed in reference services for neonatal follow-up in tertiary units of the public health system in the city of Rio de Janeiro, Brazil. Behavior was assessed using the child behavior checklist, and a structured questionnaire was used to assess sociodemographic aspects. In the bivariate analysis, prematurity was associated with externalizing problems and change in eating habits with internalizing problems. The logistic model indicated that both parents having completed high school and both sharing care of the child were protective factors for behavioral problems; however, reports of sleep problems and living with another child were risk factors. In conclusion, the study identified internalizing and externalizing behavior problems related to prematurity and aspects of family structure and routine in children at risk. The findings confirm the importance of family functioning for child health and family-centered interventions.